CAD Automation Module Based On Cell Moving Algorithm For Incremental Placement Timing Optimization - Kan, Mei War (2012)
Engineering Change Order (ECO) is a process to handle logic changes in circuit design. In deep sub-micron era, logic change in design happens inevitably. Design changes are required for numerous reasons. The reasons may be to fix design bugs, meeting design functionality change due to customer’s requirement or optimize design performance such as power consumption. An incremental placement that has the capability to handle design changes efficiently manages to save time and cost. This is why ECO remains one of the most influential steps in Very Large Scale Integration (VLSI) design. This thesis describes timing driven incremental placement that uses standard-cell move technique to improve timing of the layout design.